INFLUENCE OF DOMESTIC VIOLENCE AND PEER PRESSURE ON ADOLESCENT DELINQUENT BEHAVIOUR AMONG SOME SELECTED SECONDARY SCHOOL STUDENTS IN KEFFI TOWN - Akyo, Abdulrazak Abdullahi; Adegoke, Omolabake Oluwatomiloba; Iwuala, Caleb Chukwuebuka (African Journal of Social and Behavioural Sciences, 2024)
Delinquent behaviours in adolescence have been an increasing cause for concern in every part of the world. It is on this account, that this study aims to investigate the influence of domestic violence and peer pressure on adolescent delinquent behaviour among selected secondary school students in Keffi, Nigeria. A sample of 255 participants, comprising 130 (51%) males and 125 (49%) females participated in the study. The study made use of a survey research design and employed a structured questionnaire as a means of data collection. Descriptive statistics, hierarchical regression and Pearson correlation were used for data analysis. Results of the findings indicate that a positive correlation emerged between domestic violence and delinquent behaviour (r= .154, p<0.05), while a negative correlation was observed between peer pressure and delinquent behaviour (r= -.167, p<0.05). Furthermore, a joint predictive effect was evident, with domestic violence and peer pressure collectively impacting adolescent delinquency (R= .200, F=5.268, p<0.01). Notably, gender distinctions did not significantly influence delinquent behaviour (t= -1.501, p>0.05). In light of these results, recommendations advocate for the implementation of guidance and counselling programs tailored to adolescents, aiming to equip them with coping mechanisms for life challenges.